Aplikasi Pengolahan Data Keuangan Berbasis Website Pada CV. Berkah Property Menggunakan Metode Pengembangan Waterfall - Nanda Diaz Arizona; Yulia Yulia (Jurnal Sistem Informasi Akuntansi, 2025)
This CV. Berkah Property is a company that operates in the field of selling land plots. Inland plot purchase transactions, consumers can go directly to the office or contact the marketing department number listed on the CV brochure or social media. Berkah Property. After agreeing on the purchase, the admin will record the purchase and payment transaction in Microsoft Excel. This is certainly less effective because it can be accessed by many people. After all, there is no security for opening the document. For this reason, the author created a final assignment with the theme of creating an application entitled CV Financial Data Processing Application. Web-Based Property Blessings. The aim of making this application is to make it easier for users to process data and view the results of summary reports. This application is expected to be a solution for companies in processing financial data which initially used Microsoft Excel to become an application with a higher level of security and can make it easier for users to record financial reports